PERBEDAAN ADAT HANTARAN GAMPONG MADAT & ROT TEUNGOH KABUPATEN ACEH SELATAN - Wista Yulanda; Afrizal Tjoetra; Yenni Srilestari (Jurnal Society : Pengamat Perubahan Sosial, 2021)
This research was conducted because of differences in the customs of delivery between villages, especially in Madat Village, Samadua District and Teungoh Rot Village, Meukek District, South Aceh Regency. This difference is very influential on families with limited economies. The purpose of this study was to determine the factors causing differences in delivery customs in delivery behavior in the community in South Aceh District. The method used is a qualitative method and the determination of informants by purposive sampling with data collection techniques through interviews and documentation. The results of the study illustrate that the factors causing differences in delivery customs in Madat Village, Samadua Subdistrict, South Aceh Regency are seen in 3 (three) parts, namely economic, social and cultural. Whereas in Rot Teungoh Village, Meukek District, South Aceh Regency, it is seen in 2 (two) factors, namely culture, and customary provisions in Rot Teungoh Village.